Radiation and Thermal Decomposition Analysis in a Reactive Slab of Variable Thermal Conductivity. - Lebelo, RS; Moloi, KS; Chitumwa, CC; Adesanya, SO (International Journal of Engineering and Technology, 2018)
In this article, the impact of radiative heat loss in a stockpile of combustible material is investigated. The heat loss is attributed to the exothermic chemical reaction when the carbon containing material of the stockpile reacts automatically with the oxygen trapped within the stockpile. The study is modelled in a rectangular slab of thermal conductivity that varies with the temperature and loses heat to the surrounding environment by radiation. The differential equations governing the problem are solved numerically using the Runge-Kutta-Fehlberg (RKF) method coupled with the Shooting technique. The effect of each embedded kinetic parameter on the temperature, oxygen (O2) depletion and carbon dioxide (CO2) emission, is analyzed and the results are graphically expressed and discussed accordingly. The results show that the kinetic parameters which enhance the exothermic chemical reaction correspondingly increase the temperature and the CO2 emission during the combustion process, and in turn, these parameters also increase the depletion of O2.Â Â